ADSORPTION OF ACRIDINE ORANGE ON SOME METAL OXIDES (Biological Sciences - PJSIR, 2004)
The adsorption studies of acridine orange from aqueous solution were carried out over calcium oxide, magnesium oxide and zinc oxide. The adsorbents were subjected to a few pretreatments and the effect of pretreatment was studied on the extent and mode of adsorption. The adsorption over various pretreated surfaces exhibited three kinds of adsorption pat- tern, namely, S-type, L-type and H-type. The mode of adsorption is explained on the basis of the adsorption isotherm. The H-type is explained as flatwise adsorption with some ionic micellisation. The L-type has been interpreted as multilayer adsorption (flatwise) with the formation of large ionic micelles. The S-type has been explained as edge on (monodisperse) adsorption. The Freundlich adsorption isotherm are applicable within the limited range of concentration of dye. In few cases, these equations are not applicable due to the complex adsorption mechanism.